The postembryonic transformation of the shell in emydine box turtles. Issue 6 (23rd August 2019) - Cordero, Gerardo A.; Stearns, Samantha; Quinteros, Kevin; Berns, Chelsea M.; Binz, Steven M.; Janzen, Fredric
Abstract: A key trend in the 210‐million‐year‐old history of modern turtles was the evolution of shell kinesis, that is, shell movement during neck and limb retraction. Kinesis is hypothesized to enhance predator defense in small terrestrial and semiaquatic turtles and has evolved multiple times since the early Cretaceous. This complex phenotype is nonfunctional and far from fully differentiated following embryogenesis. Instead, kinesis develops slowly in juveniles, providing a unique opportunity to illustrate the postembryonic origins of an adaptive trait. To this end, we examined ventral shell (plastral) kinesis in emydine box turtles and found that hatchling plastron shape differs from that of akinetic‐shelled relatives, particularly where the hinge that enables kinesis differentiates. We also demonstrated shape changes relative to plastron size in juveniles, coinciding with a shift in the carapace‐plastron structural connection, rearrangement of ectodermal plates, and bone repatterning. Furthermore, because the shell grows larger relative to the head, complete concealment of the head and extremities is only achieved after relative shell proportions increase. Structural alterations that facilitate the box turtle's transformation are probably prepatterned in embryos but require function‐induced changes to differentiate in juveniles. This mode of delayed trait differentiation is essential to phenotypic diversification in turtles and perhaps other tetrapods. Abstract : Emydine turtles exhibit delayed differentiation of a shell hinge that permits shell movement or kinesis. This function‐induced transformation is characterized by substantial shell shape changes and is key to morphological diversification in turtles.